The Effect of Using the Electronic Course on the Achievement of Students of the Mathematics Department at the Faculty of Education in Afif, Saudi Arabia - Al - Otaibi, Noura Mohammed Zaker Al - Dajani (Journal of Educational and Psychological Sciences, 2018)
The objective of the research is to uncover the effect of the use of the electronic course in the development of the students of the Mathematics Department at the Faculty of Education in Afif in the curriculum of teaching techniques.In order to achieve the objectives of the research, the researcher used the experimental method and the achievement test for the curriculum of the teaching and communication techniques. The sample of the study consisted of (70) female students of the mathematics department in the Faculty of Education. (35) students. The statistical treatments were used (Holistic equation, Pearson and Spearman Brown correlation coefficients, analysis of the associated variation, effect size).The results of the study indicated that there were statistically significant differences at the mean level (0.05α) between the average scores of the students of the two groups; in the achievement test of the distance learning and communication techniques course at the levels of memory, comprehension, (18.49) and the officer and obtained an average (16.66); for the benefit of students of the experimental group at all levels. In the light of the results, the researcher made a number of recommendations to activate the use of the electronic curriculum in the teaching of mathematics and other university courses.
Keywords: impact; use; e-course; Mathematics department; Faculty of Education